Afganistan - Šterbenc, Primož (Teorija in praksa, 2023)
August 2021 saw the second takeover of the Islamist movement of the Taliban in Afghanistan, following 20 years of Western military presence. The Taliban movement first ruled the country between 1996 and 2001. In 2021, the international community was wondering whether the »students« would implement the same brutal policies towards women as they had imposed during their initial rule. Despite certain signs indicating that this time the Taliban’s policies might be different, ultimately women have become victims of the same oppression. The Taliban’s negative attitude to women is the result of several intertwined and complementary factors: ethnic, religious- ideological, social-political and inter-cultural. One cannot grasp the Taliban’s policies without taking these factors into account. However, it seems that Western actors have not understood this complex background and consequently imposed counter-productive sanctions on the Taliban regime. They have also proven unable to conduct a self-critical assessment of the consequences of the West’s protracted and problematic military presence in Afghanistan.
Keywords: Afganistan; Afghanistan; culture; Deoband; Družbeni položaj; kultura; Pashtunwali; Paštunvali; Taliban; talibani; West; Women; Zahod; Ženske